Campus sexual assault: college women respond - Germain, Lauren J. (Johns Hopkins University Press, 2016)
What we don't know about campus sexual assault - The paradox of embodied agency - Managing identity - Telling friends and family - Telling friends and family - Seeking justice - The beautiful process of empowerment - Agency and campus sexual assault